Analysis of Active Components and Antioxidant Activity of Lactobacillus casei Fermented Euryales ferox Supernatant - Yongyong YAN; Qian BIAN; Xinyu JIAO; Songlin LI (Shipin gongye ke-ji, 2022)
The changes of active components and antioxidant activity of the supernatant during Lactobacillus casei fermentation were studied using Euryales ferox as raw material. The pH, titratable acid, peptide yield, molecular weight distribution of peptides, free amino acid composition, total phenols, total flavonoids, and antioxidant activity changes of supernatant during the fermentation of Euryales ferox by L. casei were investigated, and the correlation between each component and antioxidant activity were analyzed. The results showed that during the fermentation process, the pH tended to decrease, while the titratable acid content gradually increased, reaching 3.97±0.02 and 2.53±0.04 mL/g after 48 h of fermentation, respectively. The peptide yield showed an increasing trend, reaching 19.09%±0.42% at the end of fermentation, with a significant increase in the proportion of low molecular weight peptides of 500～180 and <180 Da (P<0.05). The total amount of free amino acids increased 5.62 times during the fermentation. The content of total phenols and total flavonoids continued to increase significantly (P<0.05), reaching 18.00±0.20 and 10.99±0.14 μg/g at the end of fermentation, respectively. DPPH radical scavenging ability, hydroxyl radical scavenging ability and ferrous ion chelating ability of fermented Euryales ferox supernatant were significantly (P<0.05) increased at the end of fermentation. And the titratable acid, peptide yield, total free amino acid content, total flavonoid, and total phenolic contents had highly significant (P<0.01) positive correlations. In conclusion, the L. casei fermentation could promote the release of antioxidant active substances from Euryales ferox and significantly improve the antioxidant activity of its fermentation supernatant, which could provide a reference for the development of Euryales ferox products.